Sleep alters neurovascular and hydrodynamic coupling in the human brain - Tommi Väyrynen; Johanna Tuunanen; Heta Helakari; Ahmed Elabasy; Vesa Korhonen; Niko Huotari; Johanna Piispala; Mika Kallio; Maiken Nedergaard; Vesa Kiviniemi (Proceedings of the National Academy of Sciences, 2026)
Sleep is essential for maintaining brain tissue homeostasis, which is facilitated by enhanced cerebrospinal fluid (CSF) solute transport. Infraslow (<0.1 Hz) vasomotion, CSF flow, and electrophysiological potential all increase during sleep, but their contributions as potential drivers of CSF flow in human brain remain unknown. To investigate this, we measured these signals in healthy volunteers across sleep–wake states using functional MRI blood oxygen level-dependent (BOLD), electroencephalography, and functional near-infrared spectroscopy. We then studied the directed coupling patterns between the three signals, using phase transfer entropy. In the awake state, electrophysiological potential and water concentration changes both predicted hemodynamic BOLD changes across whole brain, reflecting classical functional hyperemia. During sleep, these interactions changed such that the net directionality was lost and the interactions became more bidirectional. Our results show that in addition to neural changes during sleep, nonneural processes such as vasomotor-driven hydrodynamic waves start to gain more impact on human brain activity.